How does social support promote professional identity among university students? A moderated mediation model of self-esteem and self-efficacy - Guangqiang Wang; Xiangyu Li; Yangbang Hu (Humanities & Social Sciences Communications)
Abstract Social support is critical for promoting professional identity among university students. However, the mechanisms and boundary conditions through which social support influences the professional identity of university students remain unclear. To address this research gap, this study aims to employ a cross-sectional design to examine the mediating role of self-esteem between social support and university students’ professional identity, as well as the moderating role of self-efficacy within the mediation model. A total of 436 Chinese university students (14.68% male and 85.32% female) participated in this study. Data analysis was conducted using Model 4 and Model 59 of the PROCESS macro program in SPSS. The results indicated that social support was significantly and positively related to both self-esteem and professional identity of university students. Self-esteem played a mediating role between social support and university students’ professional identity. Self-efficacy negatively moderated the relationship between social support and university students’ professional identity. Self-efficacy negatively moderated the relationship between social support and self-esteem. These findings enhance our understanding of the mechanisms and boundary conditions underlying the influence of social support on university students’ professional identity and provide effective recommendations for promoting this identity.